2019
DOI: 10.1534/g3.119.400201
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Traits of Long Non-protein Coding RNAs from Diverse Plant Species Show Little Evidence of Phylogenetic Relationships

Abstract: Long non-coding RNAs (lncRNAs) represent a diverse class of regulatory loci with roles in development and stress responses throughout all kingdoms of life. LncRNAs, however, remain under-studied in plants compared to animal systems. To address this deficiency, we applied a machine learning prediction tool, Classifying RNA by Ensemble Machine learning Algorithm (CREMA), to analyze RNAseq data from 11 plant species chosen to represent a wide range of evolutionary histories. Transcript sequences of all expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The highly evolved nature of lncRNAs has resulted in lower sequence conservation across plant and animal species and, thus, fewer phylogenetic relationships [38,39]. Marques and Ponting [40] reported that < 2% of lncRNAs in Arabidopsis thaliana were evolutionarily conserved across the plant kingdom, which explains the rapid evolution of lncRNA sequences.…”
Section: Sequence Conservation Diversity and Phylogenetic Features Omentioning
confidence: 99%
“…The highly evolved nature of lncRNAs has resulted in lower sequence conservation across plant and animal species and, thus, fewer phylogenetic relationships [38,39]. Marques and Ponting [40] reported that < 2% of lncRNAs in Arabidopsis thaliana were evolutionarily conserved across the plant kingdom, which explains the rapid evolution of lncRNA sequences.…”
Section: Sequence Conservation Diversity and Phylogenetic Features Omentioning
confidence: 99%
“…Across plant species, lncRNAs are reported to show low conservation and are mostly species-specific [47, 48]. Because lncRNAs are highly evolved, there is less sequence conservation across plant and animal taxa, resulting in fewer phylogenetic connections [47].…”
Section: Discussionmentioning
confidence: 99%
“…Thus over 60% of the lncRNAs that we detected in both Eutrema salsugineum ecotypes were also expressed in plants that we have no reason to believe were stressed. lncRNAs are notoriously difficult to identify with certainty and, not surprisingly, are generally poorly annotated in existing public plant reference genomes [38]. For this study we used an accurate ensemble machine learning program (CREMA [39]) that used validated lncRNAs for training.…”
Section: Discussionmentioning
confidence: 99%